“ Cenge – Cenge” Permainan Leluhur Melatih Kohesi Sosial Dan Ketangkasan Tubuh " Cenge - Cenge " Ancestral Game To Train Social Cohesion And Body Dexterity - Sarni Arta (JOURNAL OF ETHNIC DIVERSITY AND LOCAL WISDOM, 2023)
Abstract Children's games passed down from their ancestors have a very high value. Not just as ordinary entertainment, but a number of traditional games train emotional agility and the ability to build social cohesion among people, honesty, discipline, confidence, creativity and hard work. In the midst of the influence of various modern games which are getting out of control, affecting the patterns of thinking and behavior of children with various models, they are played not only among friends in one environment but across the boundaries of space and time. A number of traditional games have always been an important part of filling holidays or free time played by children in North Maluku, especially in the city of Ternate, such as boy games, sem, fort, engkrang shell, dodorobe etc. By using a qualitative descriptive approach, this research will identify and describe the types of traditional games that are still practiced in everyday life, especially in the city of Ternate, as well as traditional games that have the potential to disappear due to lack of serious attention from stakeholders at the local level.